(untitled) (Journal of history, 2022)
The history of religious figures of the late XIX – early XX centuries, who played a significant role in the spiritual history of the Kazakh people, preached traditional Islamic values, built mosques, madrasahs, schools and worked in the field of spiritual education of the Kazakh people has not yet been sufficiently studied in the national historical science. The policy of atheism alone cannot explain the fact that religious leaders in the Kazakh land became victims of merciless repression in the first years of Soviet power, which continued the colonial policy of Russian imperialism. The real reasons for this are probably the role of these religious leaders in preserving of the national code. The Bolsheviks understood that it was impossible to suppress the spirit of the nation and turn it into a mass completely subordinate to the “red empire”, without losing national identity, without destroying the Ishans, Hazrat, Kalpe and mullahs, who had a powerful influence among the people. Therefore, one of the most important tasks of historical science is an extensive study of the history of religious leaders who worked in the field of the spiritual education of the nation. Research in this area in domestic science is just beginning and is being conducted in a limited way, researching only famous religious figures or local areas. There are still many religious figures who have not found their researcher and have not been able to become the subject of research. The authors of the article strive to make their contribution to the study of this topical problem in Russian science by introducing field ethnographic materials into scientific circulation. As for the methodological basis of the research, the interdisciplinary method and the theory of “regional Islam” were used to determine the forms of development of Islam in the Kazakh steppes, the activities of traditional Islamic figures. Thus, we observe the diversity and uniqueness of traditional culture in each region and the idea of equality of local forms of Islam. Key words: traditional Islam, religious leaders, spiritual education, mosque, madrasah, maktab.